Ancaman Cybercrime di Indonesia: Tinjauan Sistematis dan Peran Cybersecurity pada E-Commerce dalam Hukum Pidana (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid development of information and communication technology in Indonesia brings serious challenges in the form of increasing cybercrime threats, especially in the e-commerce sector which is the backbone of the national digital economy. This research conducts a systematic review of various forms of cybercrime threats that threaten data security and e-commerce transactions in Indonesia, and examines the role of cybersecurity technology in mitigating these risks. In addition, this study examines the effectiveness of criminal law regulations, particularly the Electronic Information and Transaction Law (ITE Law), in tackling cybercrime. The review shows that cyber threats are increasingly complex with the emergence of artificial intelligence (AI) technology used for automated attacks and sophisticated scams such as deepfake and voice phishing. Cybersecurity plays an important role in protecting e-commerce platforms through the implementation of encryption technology, multi-factor authentication, and real-time system monitoring. However, criminal law enforcement against cybercrime still faces obstacles such as the anonymity of perpetrators and the cross-border nature of cybercrime. Therefore, a synergy between strengthening cybersecurity technology and harmonizing criminal law regulations is needed to create a safe and reliable e-commerce ecosystem in Indonesia. This research provides strategic recommendations for the government and business actors in strengthening national cyber resilience in the face of evolving threats. This theoretical study shows that the threat of cybercrime in Indonesia, especially in the e-commerce sector, is a complex phenomenon that requires a comprehensive criminal law approach and strong cybersecurity technology support. This theoretical study shows that the threat of cybercrime in Indonesia, especially in the e-commerce sector, is a complex phenomenon that requires a comprehensive criminal law approach and strong cybersecurity technology support. This research uses secondary data in the form of scientific articles, research reports, books, as well as laws and regulations related to cybercrime and cybersecurity in Indonesia, especially the ITE Law and the Criminal Code. In the context of e-commerce, cybercrime threatens customer data security, transaction integrity, and business reputation. Therefore, the role of cybersecurity becomes vital as the main fortress that protects e-commerce platforms through the implementation of encryption technology, intrusion detection systems, multi-factor authentication, and real-time monitoring.